Поширення рідкісних ранньовесняних видів флори Мурафських Товтр - Shynder, O.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
New locations of 11 rare early-vernal species of the flora of Murafa Tovtrea are described. Regional distribution of these species is considered.